Water resources planning: the activity in the Po river basin and the WFD - Fresia I.; Mitidieri E. (Food security under water scarcity in the Middle East: Problems and solutions, 2005)
Following a brief excursus of the innovative elements introduced by the WFD and the more recent Italian legislation regarding the rational management and protection of water resources, the presentation describes the activities carried out by ART to support catchment management planning, with reference to characterisation of the catchment area and analysis of the impact of human activities on water conditions (Hydrological accounting, for determination of the water accounting - Article 22 of Legislative Decree 152/99; the Eutrophication Plan for the definition of quality objectives - Article 44 of the same decree) and regarding some particularly innovative aspects that in some way anticipate national transposition of the WFD: the economic analysis and the public participation.
LNCV [Landau Network-Centro Volta] International Forum: Food Security under Water Scarcity in the Middle East: Problems and Solutions, 24-27 Nov 2004, Como (Italy)